Multimodal Pragmatic Markers of Feedback in Dialogue - Ludivine Crible; Loulou Kosmala (Languages)
Historically, the field of discourse marker research has moved from relying on intuition to more and more ecological data, with written, spoken, and now multimodal corpora available to study these pervasive pragmatic devices. For some topics, video is necessary to capture the complexity of interactive phenomena, such as feedback in dialogue. Feedback is the process of communicating engagement, alignment, and affiliation (or lack thereof) to the other speaker, and has attracted a lot of attention recently, from fields such as psycholinguistics, conversation analysis, or second language acquisition. Feedback can be expressed by a variety of verbal/vocal and visual/gestural devices, from questions to head nods and, crucially, discourse or pragmatic markers such as “okay, alright, yeah”. Verbal-vocal and visual-gestural forms often co-occur, which calls for more investigation of their combinations. In this study, we analyze multimodal pragmatic markers of feedback in a corpus of French dialogues, where all feedback devices have previously been categorized into either “alignment” (expression of mutual understanding) or “affiliation” (expression of shared stance). After describing the distribution and forms within each modality taken separately, we will focus on interesting multimodal combinations, such as [negative oui ‘yes’ + head tilt] or [mais oui ‘but yes’ + forward head move], thus showing how the visual modality can affect the semantics of verbal markers. In doing so, we will contribute to defining multimodal pragmatic markers, a status which has so far been restricted to verbal markers and manual gestures, at the expense of other devices in the visual modality.